Coastal Groundcherry, Physalis angustifolia - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Coastal groundcherry occurs on beach dunes, coastal grasslands, coastal scrub, and disturbed areas. This plant is found throughout coastal counties on the west coast of Florida—except for the Big Bend region and the extreme southeasternmost counties—and more broadly west to Louisiana. Threatened and endangered beach mice and many other animals rely on this plant as a food source. Plants can be longed-lived and form relatively thick tuberous roots. Coastal groundcherry can hybridize with other Physalis species, particularly with P. viscosa, and has long frustrated plant taxonomists because of the inherent variation within the genus (Sullivan 1985). https://edis.ifas.ufl.edu/sg180